Increasing team ideation by sequencing the task type and content. (September 2020) - Meslec, Nicoleta; Graff, Daniel; Clark, Mark A.
Abstract : While ideation is accepted as integral to the design process, the methods for facilitating ideation within teams are not as well understood. We propose and test the usefulness of sequencing variations in task type and content to facilitate team ideation in a team creativity task. In a repeated measures design we assessed team ideation (96 teams) before and after exposure to one of three randomized variations in sequences of task type and content. After this intervention, teams exposed to tasks that were dissimilar in content or type experienced the highest increase in variety of ideas produced. Our results are relevant for practice as they suggest that structuring team tasks to alternate content may help to improve team creativity. Highlights: An experimental study investigating the role of team tasks sequencing on team ideation. Tasks assigned to design teams can vary in their content or type. Task sequences that include content variety lead to better team ideation. Task sequencing as a technique to increase team ideation.